Analysis of Blockchain Security Applications in Electronic Health Records Standardization - Mishra, Princy; Khandelwal, Brijesh; Dewangan, Bhupesh K. (Recent Advances in Computer Science and Communications, 2023)
Healthcare data is most unorganized and decentralized in many countries, including India. EHR (Electronic Health Record) has increased its acceptability and importance as it assists in medical research and helps backtrack the origin of disease. EHR may be generated at multiple sources like hospitals, clinics, path labs, or pharmacies. This paper is mainly targeted towards understanding the feasibility and different processes that could be adopted for medical data security; for this purpose, we have performed a systematic literature review. This research explores existing EHR frameworks, their benefits and challenges, as well as a brief comparison and applicability of various blockchain procedures.As part of the review, we have discussed prior works, the background of blockchain in the healthcare domain, and bibliometric analysis on ample research papers from 2011 to 2021.
Keywords: SLR